Analisis Penerapan Metode Anggaran Inkremental Terhadap Efisiensi Belanja Daerah Pemerintah Kota Medan Tahun Anggaran 2025 - Novita Novita; Renny Maisyarah (Pustaka Digital Indonesia, 2026)
This study aims to analyze the implementation of the incremental budgeting method in assessing the efficiency of local government expenditure in Medan City for the 2025 fiscal year. The study employed a quantitative approach with a survey research design. The research population consisted of all Medan City Government employees involved in the budgeting process, with a sample of 100 respondents selected using purposive sampling. Primary data were collected through a questionnaire using a five-point Likert scale, which had been tested for validity and reliability (Cronbach’s Alpha > 0.70). Secondary data comprised local government expenditure realization reports from 2020 to 2024. Data were analyzed using multiple linear regression with SPSS version 26. The independent variable, incremental budgeting, was measured using indicators of percentage increase, budget stability, and the level of budget deviation. The dependent variable, local government expenditure efficiency, was measured using the efficiency ratio (realization/budget), budget absorption rate, and its impact on public service delivery. The results indicate that the implementation of the incremental budgeting method has a positive and significant effect on local government expenditure efficiency (R² = 0.624; t-value = 5.432; p-value = 0.000 < 0.05). The hypothesis was accepted at a significance level of ? = 0.05. These findings are consistent with Wildavsky’s (1964) theory, which emphasizes the advantages of the incremental approach in maintaining budget stability. This study recommends that the Medan City Government optimize additional budget allocations through stricter monitoring and the implementation of zero-based budgeting to improve the efficiency of local government expenditure. The findings are expected to provide valuable insights for accounting students and government practitioners.